Incidence of depression and anxiety in the general population of Mexico: Incidencia de depresión y ansiedad en la población general de México - Neri Vázquez, Jorge Romeo; Rodríguez López, María Guadalupe; Vargas Ruiz, Alejandro Giovanni; Ortiz Sauza, Dora Luz (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
Depression and anxiety are mental health disorders on the rise that affect 5% of the world's population, this was aggravated by the SARS COV 2 pandemic. These disorders are multifactorial, having several factors such as biological, genetic, environmental, and psychological factors that influence their development. Treatment includes cognitive behavioral therapy and antidepressants. Estimate the incidence of depression and anxiety in the general Mexican population. Provide information on the characteristics of the population studied. Methods: An observational cross-sectional study was carried out that included 2010 participants in Mexico, using surveys, the Calderón Narváez tool for the diagnosis of anxiety and depression. Surveys were conducted from April to August 2023 using online survey services and in 3 private offices in Guanajuato, Querétaro and Sinaloa. Inclusion criteria were being Mexican, being between 15 and 85 years old, and knowing how to read and write. The data collected was analyzed with IBM SPSS software. 61.9% of the population sample had a diagnosis of anxiety or some degree of depression. Self-harm in women is more common in the legs and in men in the arms. Marijuana use is associated with moderate depression, and alcohol, methamphetamine, or tobacco use was related to anxiety. This study highlights the high incidence of depression and anxiety in the Mexican population, there are differences in self-harming behaviors between both sexes, drug addictions are relevant to developing a mental disorder. These disorders are underdiagnosed.